Compensation, workload affect job satisfaction at PT ISS Indonesia South Quarter - Anggun Dwi Aliyanti; Muhammad Arif Sardi; Riad Endra Nugraha; Suhaendi (Indonesian Development of Economics and Administration Journal, 2023)
This study aimed to examine the influence of compensation and workload on employee job satisfaction at PT ISS Indonesia South Quarter. A quantitative approach was employed using associative methods. The results indicated that compensation had a significant impact on employee job satisfaction (t-value: 8.826, Sig. value: 0.000 < 0.05), supporting H1. Similarly, workload also had a significant effect on employee job satisfaction (t-value: 6.901, Sig. value: 0.000 < 0.05), supporting H2. Furthermore, when considering both compensation and workload together, they jointly influenced employee job satisfaction (F-value: 63.265, ρ-value: 0.000 < 0.05), confirming H3. These findings demonstrate that compensation and workload are important factors in determining employee job satisfaction at PT ISS Indonesia South Quarter.